Skeletal muscle transcriptomics dissects the pathogenesis of Friedreich’s ataxia - Indelicato, Elisabetta; Kirchmair, Alexander; Amprosi, Matthias; Steixner, Stephan; Nachbauer, Wolfgang; Eigentler, Andreas; Wahl, Nico; Apostolova, Galina; Krogsdam, Anne; Schneider, Rainer; Wanschitz, Julia; Trajanoski, Zlatko; et al. (Human molecular genetics, 2023)
Abstract Objective: In Friedreich’s ataxia (FRDA), the most affected tissues are not accessible to sampling and available transcriptomic findings originate from blood-derived cells and animal models. Herein, we aimed at dissecting for the first time the pathophysiology of FRDA by means of RNA-sequencing in an affected tissue sampled in vivo. Methods: Skeletal muscle biopsies were collected from seven FRDA patients before and after treatment with recombinant human Erythropoietin (rhuEPO) within a clinical trial. Total RNA extraction, 3′-mRNA library preparation and sequencing were performed according to standard procedures. We tested for differential gene expression with DESeq2 and performed gene set enrichment analysis with respect to control subjects. Results: FRDA transcriptomes showed 1873 genes differentially expressed from controls. Two main signatures emerged: (1) a global downregulation of the mitochondrial transcriptome as well as of ribosome/translational machinery and (2) an upregulation of genes related to transcription and chromatin regulation, especially of repressor terms. Downregulation of the mitochondrial transcriptome was more profound than previously shown in other cellular systems. Furthermore, we observed in FRDA patients a marked upregulation of leptin, the master regulator of energy homeostasis. RhuEPO treatment further enhanced leptin expression. Interpretation: Our findings reflect a double hit in the pathophysiology of FRDA: a transcriptional/translational issue and a profound mitochondrial failure downstream. Leptin upregulation in the skeletal muscle in FRDA may represent a compensatory mechanism of mitochondrial dysfunction, which is amenable to pharmacological boosting. Skeletal muscle transcriptomics is a valuable biomarker to monitor therapeutic interventions in FRDA.